(untitled) (AYUSHDHARA, 2020)
Enumeration of the vast number of aetiological factors (including dietetic ingredients, habits of prolonged sitting during defaecation etc.) and the systematic description of pathogenesis are indicative of scientific knowledge of the disease haemorrhoid. Its incidence has increased due to Mithyaahara- Vihara (faulty food habits and improper sedentary lifestyle). In third degree haemorrhoid pile masses prolapses during defaecation and need to be replaced manually. Ksharasootra ligation is mentioned in treatment of Arshachikitsa. In present study efficacy of Ksharasootra ligation in Arshachikitsa w.s.r. to third degree haemorrhoids Ksharasootra has been prepared using the methodology based on the description in the Ayurvedic text of 17th centaury Rasakamadhenu with some necessary modifications. Ksharasootra Ligation was done in randomly selected 15 patients of either sex with third degree haemorrhoids. The study design was open, randomized, and prospective. The duration of the trial was of 15 days, with a follow-up of 4 weeks. The total effect of therapy was assessed based on Clinical & Postoperative criteria. Statistical analysis has determined significance of the treatment. For all values significance level was p<0.05. In proctorrhagia percentage relief was 81% and results were highly significant while in prolapse percentage relief was 95%. Ksharasootra ligation had statistically highly significant and better results after treatment (p<0.001). Percentage relief in discharge per anum was 66.6% (p<0.05) and percentage relief in heaviness in the anorectal region was 80.63% with highly significant results in both complaints. According to the total effect of therapy 93.3% patients were cured while 6.6% patients were markedly improved after Ksharasootra ligation. Prolapse & Proctorrhagia (Chief clinical complaints of haemorrhoids) were almost completely cured after Ksharsootra ligation. Ksharasootra ligation results in higher degree of patient satisfaction in third-degree haemorrhoid patients. It can be concluded that Ksharasootra ligation gives almost complete relief from the symptoms of haemorrhoid.